(untitled) ((PJHAS) PUSA Journal of Hospitality and Applied Sciences, 2024)
Background: Entrepreneurship is a complex, multidimensional phenomenon that involves value creation and considered as a driving force of economic development. Entrepreneurship is one of the growing trends, and studies are focusing on it generally not only at the national but also at the global level. Objectives: To explore the cultural barriers in various Indian communities that limits the movement of women towards entrepreneurship in the hospitality business and suggest ways to overcome such barriers for women development. Methodology: The research design of the study was both qualitative and quantitative. The present study was conducted in Kolkata. The sample was collected from 43 female entrepreneur associated with various hotel oriented business using the convenience sampling technique. A well structured questionnaire was used to collect the data. Results: The study found that 32.6% of the female entrepreneurs faced financial issue as one of the biggest challenge. It was also found that 44.2% of women did not have the freedom to market the product. 25.6% of the women entrepreneurs mentioned that family commitment always affected the business performance. 44.2% of women were of the opinion that they faced psychological challenges in dealing with men in the hospitality sector. Majority of women (around 51.2%) faced problems in availing the facility of government funds whereas around (50.5%) faced challenges in loan sanctions. Conclusion: It was found that family and societal commitments and domination of men in the society in terms of business were key factors to the hindrances Support from the government and formulation of policies can be a matter of great help in this regard.